2014
DOI: 10.4012/dmj.2013-264
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the design of bio-inspired functionally graded material (FGM) layer in all-ceramic dental restorations

Abstract: Due to elastic modulus mismatch between the different layers in all-ceramic dental restorations, high tensile stress concentrates at the interface between the ceramic core and cement. In natural tooth structure, stress concentration is reduced by the functionally graded structure of dentin-enamel junction (DEJ) which interconnects enamel and dentin. Inspired by DEJ, the aim of this study was to explore the optimum design of a bio-inspired functionally graded material (FGM) layer in all-ceramic dental restorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Therefore, inspired by the structure of the DEJ, many efforts today are focusing on the development of FGCs layers, to be placed between the ceramic core and the dental cement, with the aim to grade the stiffness from the exterior to the inner part. Finite element simulations show that the presence of a FGM layer can significantly reduce the interfacial stress (up to 30%) and increase the critical crack length with the result of improved durability of the ceramic prosthesis.…”
Section: Compositional Graded Ceramics For Biomedical Applicationsmentioning
confidence: 99%
“…Therefore, inspired by the structure of the DEJ, many efforts today are focusing on the development of FGCs layers, to be placed between the ceramic core and the dental cement, with the aim to grade the stiffness from the exterior to the inner part. Finite element simulations show that the presence of a FGM layer can significantly reduce the interfacial stress (up to 30%) and increase the critical crack length with the result of improved durability of the ceramic prosthesis.…”
Section: Compositional Graded Ceramics For Biomedical Applicationsmentioning
confidence: 99%
“…15 While there are various applications of FGMs in aerospace, defense, nuclear, automotive, and other industries, FGMs also play a vital role in the medical sector. 6 Taking a wake-up look at the humans bone enhancement method, more in-depth work is needed on FGMs concerning health care, such as bone implantation, dentistry, etc.6 Cui et al investigated the optimization of functionally graded material layer architecture in all dental ceramic restorations, 16 and reported that the stress concentration in the natural tooth structure could be reduced with the help of functionally graded dentin-enamel junction which interconnects enamel and dentin. 16 This concept can be applied in all-ceramic dental restorations, for excellent stress reduction and distribution.…”
Section: Introductionmentioning
confidence: 99%
“…6 Taking a wake-up look at the humans bone enhancement method, more in-depth work is needed on FGMs concerning health care, such as bone implantation, dentistry, etc.6 Cui et al investigated the optimization of functionally graded material layer architecture in all dental ceramic restorations, 16 and reported that the stress concentration in the natural tooth structure could be reduced with the help of functionally graded dentin-enamel junction which interconnects enamel and dentin. 16 This concept can be applied in all-ceramic dental restorations, for excellent stress reduction and distribution. 16 Additionally, several experimental and numerical approaches have been utilized to investigate the thermomechanical characteristics of FGMs at bulk and microlevel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Material jetting or polyjet printing is an AM technique 10 and is capable of manufacturing different materials with different colors and properties with minimum postprocessing procedures 11–13 . Creating a bio‐inspired dental restoration that reproduces the structure and properties of human enamel and dentin has been a long‐term goal for clinical scientists 14–19 . Human tooth structure is graded with enamel being considered as an outer hard shell and dentin as a soft core 14,20,21 .…”
mentioning
confidence: 99%